CGIAR research program (CRP) on roots, tubers, and bananas: Rationale, strategy and impact. - Thiele, Graham (2012)
The CRP recognizes that research must embrace a broad portfolio of commodities beyond the grain crops that have traditionally been the focus of food security initiatives. Roots, tubers, and cooking bananas and plantains are a critical component of the global food system. As vegetatively propagated crops they have many similarities for genetic conservation, breeding strategies, seed systems and post-harvest technology. The program is led by the International Potato Center, Bioversity International, the International Center for Tropical Agriculture, and the International Institute for Tropical Agriculture and includes a wide spectrum of research-for-development stakeholders. This new collaboration, with its combined scale and capacity, will increase the ability to advance research, share knowledge, and enhance impact. The program strategy is to exploit the underutilized potential of root, tuber, and banana crops to reduce the risk of food shortages and malnutrition through increased yields and stronger, more diversified crop systems. In addition, the CRP aims to increase income generation and foster greater gender equity. The CRP has identified impact pathways to increase the likelihood that research is translated into improved livelihoods – especially among some of the world's most poor and vulnerable populations. In its first year of operation, it is quantifying potential impacts to help priority setting. Engaging partners and stakeholders will be critical to successful implementation.